The Influence of Liquidity, Profitability, and Asset Growth on Dividend Policy - Febrianty, Erica; Kusumastuti, Ratih (Invoice : Jurnal Ilmu Akuntansi, 2024)
This study aims to determine the effect of liquidity, profitability, asset growth on Dividend Policy in sub-companies of the property and real estate listed in Indonesia Securities in 2018-2021. The independent variable in this study is dividend policy calculated using the divident payout ratio model, and the dependent el variab in this study is liquidity ratio (current ratio), profitability (return on equity), and asset growth (asset growth). Sample determination was carried out by purposive sampling technique with the number of selected samples as many as 11 companies from a population of 67 companies. This study used multiple regression analysis methods and classical assumption tests.  The software used for data processing is IBM SPSS 26. The results of this study are 1) liquidity negatively affects dividend policy. 2) Profitability has a positive effect on dividend policy. 3) Asset growth has a positive effecton dividend policy. The results of this study contribute to the development of theories regarding dividend policy for investors and companies, companies that pay dividends periodically are considered superior to companies that do not consistently pay dividends.